Multilevel governance and Smart Specialization in EU regions: an evidence-based critical review - Eristian Wibisono (European Journal of Government and Economics, 2022)
This paper critically reviews the literature on multilevel governance issues in support of implementing Smart Specialization policies in EU regions. Using an evidence-based critical review approach, key literature that draws on three critical concepts is explored: multilevel governance, regional innovation policy, and Smart Specialization in various governance conditions and diverse regional resources. The evidence reviewed points to the critical role of multilevel governance in implementing Smart Specialization. Effective coordination mechanisms are essential building blocks to encounter the challenges of multilevel governance for Smart Specialization. More consequential, however, are substantial synergies that are solid, harmonious, and balanced among multi-stakeholders within institutions and across levels of government. This paper contributes to the limited literature on multilevel governance in support of the Smart Specialization policy. Further studies considering different types of regions are recommended to enrich future literature.